PENGARUH MINAT BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS PADA MATA KULIAH TEORI BILANGAN MAHASISWA PENDIDIKAN MATEMATIKA - Rais, Hidayati (STKIP YPM Bangko, 2019)
This study aims to find out and describe the significant effect of interest in learning on understanding mathematical concepts in the number theory course of STKIP YPM Bangko mathematics education college students. This type of research is a quantitative approach with a correlational method. The population of the study was the first semester college students of the 2018/2019 academic year mathematics education totaling 18 people. Sampling uses a saturated sampling technique. The data collection technique is a test of understanding mathematical concepts in number theory courses in the form of essay questions and learning interest questionnaires using a Likert scale. The data analysis technique uses the normality test and linearity test, while thehypothesis test uses the Pearson product moment correlation formula and the significance test using the t-test formula. The results of the analysis of sample class data obtained a correlation coefficient with a sig value = 0.952. While the contribution of the relationship between the variables of interest in learning and understanding of mathematical concepts are grouped very high at 90.630% and hypothesis testing obtained tcount = 12.404 at the significance level α = 0.05 with tcount > ttabel or 12.404 > 1.746 then Ha is accepted and Ho is rejected. This means that there is a significant influence between interestin learning towards understanding mathematical concepts in the number theory course of STKIP YPM Bangko mathematics education college students.Keywords: Interest in Learning and Understanding of Mathematical Concepts.